Odpowiedź:
(x² + a)(x² + bx + c) = 0
a = - 3 , b = - 2 , c = - 6
(x² - 3)(x² - 2x - 6) = 0
(x - √3)(x + √3)(x² - 2x - 6) = 0
x² - 2x - 6 = 0
a = 1 , b = - 2 , c = - 6
Δ = b² - 4ac = (- 2)² - 4 * 1 * (- 6) = 4 + 24 = 28
√Δ = √28 = √(4 * 7) = 2√7
x₁ = ( - b - √Δ)/2a = (2 - 2√7)/2 = 2(1 - √7)/2 = 1 - √7
x₂ = (- b + √Δ)/2a = (2 + 2√7)/2 = 2(1 + √7)/2 = 1 + √7
równanie ma postać
(x - √3)(x + √3)(x - 1 + √7)(x + 1 + √7) = 0
x = √3 ∨ x = - √3 ∨ x = 1 - √7 ∨ x = 1 + √7
Równanie ma 4 rozwiązania , z których żadne nie jest liczba całkowitą